Analisis Faktor yang Mempengaruhi Waktu Tunggu terhadap Kepuasan Pelayanan Resep Pasien Rawat Jalan - Nurul Lailia Utami; Musa Ghufron (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Waiting time in outpatient prescription services is a critical indicator directly influencing patient satisfaction. This study aims to analyze factors affecting waiting time and its relationship with patient satisfaction. The research employed a narrative literature review method, reviewing 16 national and international journal articles published between 2018 and 2023. Data were collected through searches in Google Scholar, PubMed, ScienceDirect, EBSCO, and SpringerLink databases using relevant keywords. Data analysis was conducted descriptively and thematically. Results indicate that internal factors such as the number and competence of human resources, workflow efficiency, and availability of infrastructure significantly affect waiting time. External factors include patient volume, patient characteristics, waiting room facilities, and institutional policies. A strong relationship between shorter waiting time and higher patient satisfaction was also identified. The conclusion recommends interventions such as staff augmentation, queue digitalization, and facility improvement to enhance service quality. Further research with qualitative and longitudinal approaches is suggested to deeply explore psychosocial aspects and technology innovation effectiveness.